2016
DOI: 10.1074/jbc.m115.694810
|View full text |Cite
|
Sign up to set email alerts
|

Formation and Reversibility of BiP Protein Cysteine Oxidation Facilitate Cell Survival during and post Oxidative Stress

Abstract: Redox fluctuations within cells can be detrimental to cell function. To gain insight into how cells normally buffer against redox changes to maintain cell function, we have focused on elucidating the signaling pathways that serve to sense and respond to oxidative redox stress within the endoplasmic reticulum (ER) using yeast as a model system. Previously, we have shown that a cysteine in the molecular chaperone BiP, a Hsp70 molecular chaperone within the ER, is susceptible to oxidation by peroxide during ER-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
91
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(94 citation statements)
references
References 64 publications
3
91
0
Order By: Relevance
“…We reported previously that addition of select Kar2 Cys63 mutant alleles allows for enhanced cell viability during cellular oxidative stress [1, 2]. These prior experiments built upon our observation that a strain containing a kar2-C63A allele was compromised for growth in the presence of exogenous or endogenous oxidants, relative to a strain containing wild-type Kar2 [1].…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations
“…We reported previously that addition of select Kar2 Cys63 mutant alleles allows for enhanced cell viability during cellular oxidative stress [1, 2]. These prior experiments built upon our observation that a strain containing a kar2-C63A allele was compromised for growth in the presence of exogenous or endogenous oxidants, relative to a strain containing wild-type Kar2 [1].…”
Section: Resultsmentioning
confidence: 93%
“…It has been demonstrated for both mammalian and yeast BiP that during conditions of increased ER oxidation, this cysteine becomes oxidized, which in turn augments BiP chaperone activity [1, 2, 20]. Such an alteration in BiP activity is thought to benefit cells during oxidative stress by limiting polypeptide aggregation during suboptimal redox conditions for ER protein folding.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…82 Recently, it could be shown that also yeast BiP, an Hsp70 in the ER, has a cysteine which can be glutathionylated and cause enhanced chaperone holdase activity. 92 Additionally, an activating thiol-based redox switch was observed for Hsp33 of E. coli, where oxidation of Hsp33 leads to chaperone activation. 83 Taken together, the increasing number of observations that chaperones are subject to redox-regulation of their activities offers new possibilities for therapeutic intervention for neurodegenerative diseases Methods to analyze redox capacity…”
Section: Redox-regulation Of Chaperonesmentioning
confidence: 99%